2015
DOI: 10.3109/10520295.2014.998282
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of salivary nitric oxide in oral precancer patients

Abstract: The role of nitric oxide (NO) in the initiation, promotion and progression of cancer has been the subject of speculation and conflicting reports in the literature. The high incidence of oral cancer and precancer has been linked to tobacco chewing and smoking habits; NO is considered an indicator of tobacco-related diseases. We compared salivary NO levels in oral precancer and normal patients. Unstimulated whole saliva was collected from 15 patients with oral precancer (group 1) and 15 healthy age and sex match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…18 Senthil et al 19 showed that low levels of caries in children is related to increase in NO levels. Metgud et al 20 showed that extreme increase in NO can have a destructive and inflammatory effect in the oral cavity. For example, oral lichen planus is a chronic inflammatory process in which NO produced by L-arginine amino acid by NO synthase enzyme has an important role.…”
Section: Discussionmentioning
confidence: 99%
“…18 Senthil et al 19 showed that low levels of caries in children is related to increase in NO levels. Metgud et al 20 showed that extreme increase in NO can have a destructive and inflammatory effect in the oral cavity. For example, oral lichen planus is a chronic inflammatory process in which NO produced by L-arginine amino acid by NO synthase enzyme has an important role.…”
Section: Discussionmentioning
confidence: 99%
“…As the population becomes older, the prevalence of head and neck cancer in people aged 65 and above in the Western world will increase by 27% from 2020-2030 [ 28 ]. It was shown by the statistics of inpatients in oral and maxillofacial surgery that the leading disease over 65 years old was oral and maxillofacial tumors, followed by salivary gland diseases, and malignant tumors were significantly more than benign tumors [ 29 ]. Oral and maxillofacial malignant tumors mainly occur in the mouth, followed by salivary glands and neck, the main tumor sites of oral cancer were tongue and palate, accounting for about 40.2% [ 30 ].…”
Section: Dental Aging-related Diseasesmentioning
confidence: 99%
“…C) using an ELISA kit (Novus kits, Novus Biologicals, LLC, California, USA). At the end of the experiment, the colon of each animal was excised, washed with phosphate-buffer saline (PBS), gently stretched, and the distance between the colocecal junction and the distal end of the rectum was measured 40 . The distal sections of the colons were then separated; one piece was used for histopathological analysis, and the other piece was kept frozen at 80 • C until biochemical analysis of TBARS, GSH, SOD, and CAT 41-44 using colorimetric methods in the diagnostic kit.…”
Section: Sample Collectionmentioning
confidence: 99%